Spirometry performed as part of the Manchester community-based lung cancer screening programme detects a high prevalence of airflow obstruction in individuals without a prior diagnosis of COPD. Issue 8 (22nd May 2020) - Balata, Haval; Harvey, Jonathan; Barber, Phil V; Colligan, Denis; Duerden, Rebecca; Elton, Peter; Evison, Matthew; Greaves, Melanie; Howells, John; Irion, Klaus; Karunaratne, Devinda; Mellor, Stuart; et al.
Abstract : Background: COPD is a major cause of morbidity and mortality in populations eligible for lung cancer screening. We investigated the role of spirometry in a community-based lung cancer screening programme. Methods: Ever smokers, age 55–74, resident in three deprived areas of Manchester were invited to a 'Lung Health Check' (LHC) based in convenient community locations. Spirometry was incorporated into the LHCs alongside lung cancer risk estimation (Prostate, Lung, Colorectal and Ovarian Study Risk Prediction Model, 2012 version (PLCOM2012 )), symptom assessment and smoking cessation advice. Those at high risk of lung cancer (PLCOM2012 ≥1.51%) were eligible for annual low-dose CT screening over two screening rounds. Airflow obstruction was defined as FEV1 /FVC<0.7. Primary care databases were searched for any prior diagnosis of COPD. Results: 99.4% (n=2525) of LHC attendees successfully performed spirometry; mean age was 64.1±5.5, 51% were women, 35% were current smokers. 37.4% (n=944) had airflow obstruction of which 49.7% (n=469) had no previous diagnosis of COPD. 53.3% of those without a prior diagnosis were symptomatic (n=250/469). After multivariate analysis, the detection of airflow obstruction without a prior COPD diagnosis was associated with male sex (adj OR 1.84, 95% CI 1.37 to 2.47; p<0.0001), younger age (p=0.015), lower smoking duration (p<0.0001), fewer cigarettes per day (p=0.035), higher FEV1 /FVC ratio (<0.0001) and being asymptomatic (adj OR 4.19, 95% CI 2.95 to 5.95; p<0.0001). The likelihood of screen detected lung cancer was significantly greater in those with evidence of airflow obstruction who had a previous diagnosis of COPD (adj OR 2.80, 95% CI 1.60 to 8.42; p=0.002). Conclusions: Incorporating spirometry into a community-based targeted lung cancer screening programme is feasible and identifies a significant number of individuals with airflow obstruction who do not have a prior diagnosis of COPD.